Comparative diagnostic efficacy of biopsy strategies for prostate cancer detection: a Bayesian network meta-analysis of 24 randomised controlled trials. (December 2017) - Yang, Lu; Qiu, Shi; Deng, Linghui; Bian, Haiyang; Tobias, Ian Charles; Huang, Chengyi; Liu, Liangren; Liu, Zhenhua; Bao, Yige; Wei, Qiang
Abstract: Background: The introduction of three kinds of MRI-guided prostate biopsies (MRI-PB) has changed the model of practice regarding prostate biopsies. The most appropriate strategy is still unknown, we therefore aimed to compare and rank prostate biopsies strategies. Methods: We did a network meta-analysis to incorporate both direct and indirect evidence from relevant trials. We searched PubMed, the Cochrane Library Central Register of Controlled Trials, Scopus, Embase, and the reference lists of relevant articles for randomised controlled trials published up to Sept 1, 2016, of different strategies for prostate biopsy. Involved studies were full text reports of randomised trials that compared different biopsy strategies, and reported efficacy endpoints. The primary outcome was overall prostate cancer detection rate. We did pairwise meta-analyses by random effects model and network meta-analysis by Bayesian random effects model. We assessed the quality of evidence contributing to each network estimate using the GRADE framework. This study is registered with PROSPERO, number CRD42016044011. Findings: From a total of 3616 citations, 24 randomised trials with a total of 6497 participants were included in this network meta-analysis. We considered 11 strategies of prostate biopsy published between 2000 and 2016. Cognitive MRI prostate biopsy was significantly better (relative risk [RR] 2·66, 95% credible interval [CrI] 1·44–4·72) than TRUS (10-12; PCa detection from 10–12 needle core transrectal ultrasound prostate biopsy) prostate biopsy considering overall prostate cancer detection rate. Detection rates of clinically significant and insignificant prostate cancers suggested no significant difference between any group of all biopsy techniques. Interpretation: Although cognitive MRI prostate biopsy obtained better detection rates of overall prostate cancer than did TRUS (10-12) prostate biopsy, it had no remarkable advantages in detection of clinically significant and insignificant prostate cancers. Nevertheless, these results should be considered together with all known safety and economy information when selecting the strategy for individual patients. Funding: This study was supported by the Prostate Cancer Foundation Young Investigator Award 2013, the National Natural Science Foundation of China (81300627, 81370855) and Programs from Science and Technology Department of Sichuan Province (2013SZ0006, 2014JY0219).